Seeing like the Buddha: enlightenment through film - Cho, Francisca (State University of New York Press, 2017)
List of Illustrations; Acknowledgment; Abbreviations; Chapter 1 Seeing Like the Buddha; Erasing the Buddha; The Necessity of Form; Visions of the Buddha; Conclusion; Chapter 2 The Karmic Narrative of Spring, Summer, Fall, Winter . . . and Spring; Observing the Buddhist Drama; The Bodhisattva's Vision; Repetition and Awakening; The Collapse of Time; Chapter 3 The Meditative Discernment of Nang Nak; The Karma of Ghosts; The Buddhist Taming; The Eye of Wisdom; Keeping It Real; Chapter 4 Rashomon and the Indiscernible Emptiness of Being; Buddhist Origins; The Subjectivity of Perception